Anticipated regret and organ donor registration: a randomised controlled trial - O'Carroll, Ronan E.; Shepherd, Lee; Hayes, Peter C.; Ferguson, Eamonn (American Psychological Association, 2016)
Objective: To test whether simply asking people to rate the extent to which they anticipate feeling regret for not registering as an organ donor after death increases subsequent verified organ donor registration. Methods: 14,509 members of the general public (both registered and non-registered donors) were randomly allocated to 1 of 4 arms, each receiving different questionnaires. The no-questionnaire control (NQC) arm received a survey measuring demographics and whether or not they were registered organ donors. The questionnaire control (QC) arm completed the NQC questions plus questions regarding affective attitudes and intention to register as an organ donor. The theory of planned behaviour (TPB) questionnaire arm received the QC questionnaire, plus additional items measuring TPB variables. The anticipated regret (AR) arm received the TPB questionnaire, plus two additional items measuring anticipated regret. The main outcome measures were number of non-donor participants who subsequently registered six months later, as verified by the UK national transplant register. Results: Intention-to-treat (ITT) analysis in non-registered donors (N = 9,139) revealed the NQC arm were more likely to register as an organ donor (6.39%) compared to the AR (4.51%) arm. Conclusions: A brief anticipated regret intervention led to a decrease in registration. A potential reason is discussed in terms of questionnaire item content “priming” negative perceptions of organ donation. This is a methodological concern that needs to be addressed in studies that use similar interventions. Current controlled trials: www.controlled-trials.com number: ISRCTN922048897.